Effects of Dy substitution for Bi on phase, microstructure and dielectric properties of layer-structured Bi4-xDyxTi3O12ceramics - Navavan Thongmee (2018)
Bi4-xDyxTi3O12(when x = 0, 0.25, 0.5, 0.75 and 1.0) powders and ceramics were prepared by solid-state mixed oxide method. The calcination was carried out at 900°C for 4 h with heating/cooling rate 5°C/min. The ceramics were then sintered at a temperature between 950-1100°C for 4 hrs. The optimum sintering temperature was found to be 1000°C. X-ray diffraction indicated the existence of orthorhombic phase for all sintering temperatures. Scanning electron micrographs of ceramic surfaces showed a plate-like structure with different grain size. The results of room temperature dielectric constant revealed that Dy dopant could dielectric constant of Bi4Ti3O12ceramic where it was optimized at x = 0.25. © 2014 Copyright Taylor and Francis Group, LLC.